Exchange bias and surface effects in bimagnetic CoO-core/Co0.5Ni0.5Fe2 O4 -shell nanoparticles - Lavorato, Gabriel Carlos (2016)
Bimagnetic nanoparticles have been proposed for the design of new materials with controlled properties, which requires a comprehensive investigation of their magnetic behavior due to multiple effects arising from their complex structure. In this work we fabricated bimagnetic core/shell nanoparticles formed by an ∼3-nm antiferromagnetic (AFM) CoO core encapsulated within an ∼1.5-nm ferrimagnetic (FiM) Co0.5Ni0.5Fe2O4 shell, aiming at studying the enhancement of the magnetic anisotropy and the surface effects of a ferrimagnetic oxide shell. The magnetic properties of as-synthesized and annealed samples were analyzed by ac and dc magnetization measurements. The results indicate that the magnetic response of the as-synthesized particles is governed by the superparamagnetic behavior of the interacting nanoaggregates of spins that constitute the disordered ferrimagnetic shell, whose total moments block at (TB)=49 K and collectively freeze in a superspin-glass-type state at (Tg)=3 K. On the other hand, annealed nanoparticles are superparamagnetic at room temperature and behave as an exchange-coupled system below the blocking temperature (TB)=70 K, with enhanced coercivity HC(10K)∼14.6 kOe and exchange bias field HEB(10K)∼2.3 kOe, compared with the as-synthesized system where HC(10K)∼5.5 kOe and HEB(10K)∼0.8 kOe. Our results, interpreted using different models for thermally activated and surface relaxation processes, can help clarify the complex magnetic behavior of many core/shell and hollow nanoparticle systems.